Paradox of Expanding Renewable Energy Resources: Legal Lag Behind the Advancement of Digital Technology - Nur Hidayani Alimuddin; Riezka Eka Mayasari; Jusafri Jusafri; Muhammad Riyan Kachfi Boer (Journal of Law and Legal Reform, 2024)
Advances in digital technology have brought massive changes to various aspects of life, including managing natural resources in renewable energy. Digital technology has become one of the strongest drivers for the energy transition goal. In light of this potential, various government policies are currently underway to facilitate the expansion of these resources. Initially, this expansion initiative appears to be a sound and perfect plan, as the transition towards renewable energy will significantly affect environmental conservation efforts, bolstered by digitalization in the energy management sector. Holistically, there appears to be some confusion from both social and economic perspectives, and particularly from a legal perspective at the regulatory level. Objective of this research is to investigate the relationship between advancements in digital technology on renewable energy expantion. Additionally, it aims to investigate the legal barriers that hinder efforts to expand renewable energy in the country, and to explore the significance of paradoxes in this process. This research was conducted principles of law, synchronisation regulations, historical legal analysis, and comparative jurisprudential study. The findings of the research indicate that digital technology, or digitization, in the management of renewable energy provides a significant positive contribution in terms of improving safety, production processes, increasing access, and sustainable management. On the other side, renewable energy regulations have not been able to accommodate the country's expansion efforts and potential. There are still many legal, social, economic, and environmental conflicts in this process.